1996
DOI: 10.1002/chin.199607256
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: A Novel Verbascoside‐Like Ester Glycoside from the Leaves of Digitalis lanata Ehrh. Maxoside (I)

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…, was reported as a phenylethyl glycoside from D. lanata [9], while some members of the genus have been investigated in terms of their phenylethyl glycoside contents [10 -13]. As a continuation of our work on the phenylethyl glycosides from medicinal plants, we investigated the secondary metabolites of D. lanata, primarily focusing on its phenylethyl glycoside composition.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…, was reported as a phenylethyl glycoside from D. lanata [9], while some members of the genus have been investigated in terms of their phenylethyl glycoside contents [10 -13]. As a continuation of our work on the phenylethyl glycosides from medicinal plants, we investigated the secondary metabolites of D. lanata, primarily focusing on its phenylethyl glycoside composition.…”
mentioning
confidence: 99%
“…After partition between H 2 O and organic solvents, the H 2 O-soluble part of the MeOH extract was submitted to multiple chromatographic steps to afford three new phenylethyl glycosides, 1 -3, in addition to seven known metabolites. The known compounds were identified as purpureaside A [10], maxoside [9] [14], cornoside [15], lanatoside C [7], purpureagitoside [3], and sucrose [16] 2) secured by 2D-NMR analyses and comparison with those of maxoside [9], the structure of 1 was identified as 2- C-NMR spectrum. The NMR data of 1 were almost the same as those of maxoside [9], except for the presence of signals at d 3.93 and 56.2 arising from the MeO group in the NMR spectra of 1.…”
mentioning
confidence: 99%
“…A part of the BuOH extract was passed through a porous‐polymer polystyrene resin ( Diaion HP‐20 ) column, and the fraction eluting with 50% MeOH was subjected to silica gel column chromatography (CC) to afford three new phenylethanoid glycosides, 1 – 3 , in addition to five known compounds. The known glycosides were identified as purpureaside B , 3′′′′‐ O ‐methylmaxoside , purpureaside E , maxoside , and chionoside F , by comparison of their spectroscopic data with literature values.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of three anomeric H‐ and C‐atoms ( δ 4.41 ( d , J = 7.8 Hz) and δ 103.6; δ 4.39 ( d , J = 8.0 Hz) and δ 105.5; δ 4.34 ( d , J = 7.9 Hz) and δ 104.7) was typical for three β ‐linked glucopyranosyl units. The NMR data of 3 were found to be similar to those of maxoside , except for the additional ( E )‐feruloyl signals in 3 (three aromatic H‐atoms as an ABX system at δ 7.19 ( d , J = 2.0 Hz), 7.08 ( dd , J = 8.0 and 2.0 Hz), and 6.82 ( d , J = 8.0 Hz), two ( E )‐olefinic H‐atoms as an AB system at δ 7.64 and 6.39 ( d , J = 16.0 Hz), and a MeO group at δ 3.87 ( s )). The downfield shifts for the CH 2 (6 ′′′ ) ( δ 4.52 and 4.32) and C(6 ′′′ ) signals ( δ 64.8) and the upfield shift for the C(5 ′′′ ) signal ( δ 77.5) confirmed that the esterification site for the ( E )‐feruloyl unit was at HO–C(6 ′′′ ), which was further supported by the three‐bond correlation of CH 2 (6 ′′′ ) to the C(9 ′′′′′ ) group at δ 168.4 of the feruloyl unit in the HMBC spectrum ( Fig .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation